2021
DOI: 10.1017/s002202992100039x
|View full text |Cite
|
Sign up to set email alerts
|

Why knowledge is the best way to reduce the risks associated with raw milk and raw milk products

Abstract: In an age of flexible conditions about mandatory milk pasteurisation, this opinion-based research reflection supports the view that the knowledge and the awareness of milk-borne infections are key requirements to decrease the risks associated with raw milk. Providing an analysis of the current potential risks related to consumption of raw milk and raw milk products, we discuss the main reasons to continue to be vigilant about milk-borne pathogens and the current scenario in relation to the formal and clandesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Again, knowledge about diseases transmitted by raw milk was the only factor that was significantly (P < 0.05) associated with the level of total bacterial count among milk transporters in Nyagatare district as illustrated Table 6. This agree with the study of [17] who reported that the awareness of the diseases that can be transmitted by raw milk, is essential in reducing the hazards associated with drinking raw milk.…”
Section: Resultssupporting
confidence: 92%
“…Again, knowledge about diseases transmitted by raw milk was the only factor that was significantly (P < 0.05) associated with the level of total bacterial count among milk transporters in Nyagatare district as illustrated Table 6. This agree with the study of [17] who reported that the awareness of the diseases that can be transmitted by raw milk, is essential in reducing the hazards associated with drinking raw milk.…”
Section: Resultssupporting
confidence: 92%
“…Drinking raw or unpasteurised camel milk has been an integrated traditional belief for the people of the UAE. However, a large body of strong evidence confirms that raw milk is not recommended for consumption due to increased risks of foodborne diseases (36,37) . In the present study, an alarming proportion of consumers reported drinking raw camel milk without heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of milk treatment was unexpectedly related to location. People with awareness of the risk of milk-borne pathogens were twice less likely to contract abdominal illness than those who were unaware [32]. Consequently, the responsible organizations should spread knowledge on adequate milk treatment protocols.…”
Section: Discussionmentioning
confidence: 99%